ANALISIS PEMBIAYAAN BAI’INAH, DEPOSITO MUDHARABAH, DAN SIMPANAN WADIAH TERHADAP BAGI HASIL DI BMT NU Al-MA’WA CILACAP - Muhamad Rijal Pamungkas; Khamimatus Sodiqoh (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2022)
The objectives of this study are (1) to determine the effect of Bai'inah financing on profit sharing (2) to determine the effect of Mudharabah deposits on profit sharing (3) to determine the effect of Wadiah deposits on profit sharing (4) to determine the effect of Bai'inah financing, Mudharabah deposits, and Wadiah savings simultaneously against profit sharing. The data used are time series data for profit sharing, Bai'inah financing, Mudharabah deposits, and Wadiah deposits for the period January 2017 - December 2019 at BMT NU Al-Ma'wa Cilacap. The data analysis technique used multiple linear regression analysis. For multiple linear regression analysis the variable instrument is (1) the dependent variable Y is profit sharing, (2) the independent variable X1 is Bai'inah financing, (3) the independent variable X2 is Mudharabah deposits, (4) the independent variable X3 is Wadiah savings. The results of this study, the independent variable bai'inah financing (X1), the independent variable mudharabah deposit (X2), and the independent variable wadiah savings (X3) affect the dependent variable for the results (Y) either partially or simultaneously. Furthermore, suggestions for BMT NU Al-Ma'wa Cilacap in developing and improving their well-performing businesses, this increase could be through social media advertising or opening new branches in potential locations.